Civil-military relations in the Islamic world - Lenze, Paul E. (Lexington Books, 2016)
The book examines civil-military relations in key Middle Eastern and South Asian Islamic states. Specifically it analyzes how the endurance of authoritarianism in Algeria, Egypt, Pakistan, and Turkey is affected by international influence on the political development of these states.